The Fight for Flight - Arnold, Nick (Horrible Science, 2008)
Readers will will be blown away by how to see the earth's shadow, how to build a flying saucer, and how, after centuries of fearsome flight flops, people have finally taken to the skies. With a fantastic new cover look and extra horrible bits, this best-selling title is sure to be a huge hit with a new generation of Horrible Science readers.